2018
DOI: 10.1016/j.conbuildmat.2018.05.191
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effects of hooked-end steel fibre geometry on the uniaxial tensile behaviour of self-compacting concrete

Abstract: A series of uniaxial tensile tests on cylinders made from steel fibre reinforced selfcompacting concrete (SFR-SCC) have been carried out to investigate the influence of fibre geometry and the combined effect of fibre content and distribution on the post-cracking behaviour. Three types of commercially available hooked end fibres (3D (single hooked), 4D double (double hooked) and 5D (triple hooked)) have been used in this study, which are added to the concrete mixture at two fibre dosages (0.5 and 1% by volume).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…3 D, 4 D and 5 D) designated as Dramix V R has been widely reported. [29][30][31] Ghasemi et al 29 have reported the effects of distinct steel fiber proportions in a SCC (i.e. 0.1, 0.3 and 0.5% corresponding with 7.8, 23.5, and 39 kg/m 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 D, 4 D and 5 D) designated as Dramix V R has been widely reported. [29][30][31] Ghasemi et al 29 have reported the effects of distinct steel fiber proportions in a SCC (i.e. 0.1, 0.3 and 0.5% corresponding with 7.8, 23.5, and 39 kg/m 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the same fiber volume fraction, the 5D hooked-end fibers have the best flexural performance including the load-carrying capacity and post-peak ductility, followed by the 4D and 3D hooked-end fibers, respectively. This is mainly caused by their better pullout resistance, i.e., higher bond strength and pullout work, as reported by some previous studies [10][11][12]. The higher number of hook ends requires a higher force to bend more plastic hinges; hence, the 5D hooked-end fiber had the highest pullout resistance, followed by the 4D and 3D fiber, based on an assumption that the cement matrix was strong enough.…”
Section: Mechanical Propertiesmentioning
confidence: 60%
“…Such a superior bond performance is achieved because of the improved mechanical anchorage, owing to the increased number of hook ends. The peak and post-peak tensile strengths of steel fiber-reinforced concrete (SFRC) with conventional 3D hooked-end fibers were significantly enhanced by using the 4D and 5D hooked-end fibers, according to a previous study performed by Abdallah et al [11]. The 5D hooked-end fiber specimen only exhibited a re-increase in tensile stress (hardening) after a sudden drop in the stress by matrix cracking because of its stronger pullout resistance than the others (i.e., 3D and 4D hooked-end fibers).…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations